Welding equipment modernization - Kosimova Zamira Medatovna; Dzhemilov Denis Igorevich (International Journal on Human-Computing Studies, 2021)
This article deals with the automation problems of welding production, the RTC composition. It was selected specific robotic systems, parameters which are versatile and suitable for most products.